Effects of an Islamic-based gratitude strategy on Muslim students’ level of happiness - Al-Seheel, Ali Youssef; Mohd Noor, Noraini (Routledge Taylor & Francis Group, 2016)
This study examined the effects of an Islamic-based expressive gratitude strategy in comparison to a secular-based expressive gratitude strategy and a control group in enhancing Muslims’ level of happiness. It was hypothesised that practising the Islamic-based gratitude exercise (by associating blessings with Allah) would result in higher happiness level over time, compared to the happiness level of Muslim participants practising the secular-based gratitude exercise (without specific association) or the control group (attending to details of daily life). Sixty students were randomly assigned into one of three groups and over a period of 16 days were asked to practise the respective exercises daily. They were assessed for pre- and post-happiness measures. Results generally supported the hypothesis, and suggested that the Islamic-based gratitude is beneficial in raising participants’ happiness level, as it fits with their beliefs and values. Implications of the results for including Islamic-oriented intervention to promote Muslim happiness are discussed